Hak Masyarakat Adat dalam Perspektif Keadilan Sosial Pancasila - St. Ika Noerwulan Fraja; Fendi Setyawan; Dominikus Rato (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This article examines the rights of Indigenous Peoples from the perspective of Pancasila’s social justice by positioning Pancasila as the philosophical foundation for the protection of communal rights. The research employs a normative juridical method with philosophical and statutory approaches. The findings indicate that the values of social justice, humanity and national unity embodied in Pancasila provide a normative basis for the recognition and protection of Indigenous Peoples’ rights. However, their implementation continues to face various challenges, including regulatory constraints, exploitative development orientations and weak legal recognition mechanisms. Therefore, stronger regulatory frameworks and policies that are more aligned with the values of Pancasila’s social justice are required to ensure the sustainable protection of Indigenous Peoples’ rights.